Intermittent Ureteropelvic Junction Obstruction Can Mimic Abdominal Migraine: A Case Report and Review of the Literature - Yasaman Daryabari; Parmida Sadat Pezeshki; Negar Mohammadi Ganjaroudi; Abdol‐Mohammad Kajbafzadeh (Clinical Case Reports)
ABSTRACT Recurrent abdominal pain poses a diagnostic challenge in the pediatric population. Functional and structural etiologies can contribute to this condition. The organic etiologies of recurrent abdominal pain are diagnoses of exclusions and considering them as the initial diagnosis could lead to mis‐ or delayed diagnosis with potentially several clinical consequences. Intermittent ureteropelvic junction obstruction (UPJO) is one of the structural etiologies of recurrent abdominal pain that could mimic the clinical presentation of functional etiologies. The absence of radiologic evidence of intermittent UPJO in the interval between the attack episodes makes it a diagnostic challenge, especially in the initial stages. This underscores the value of imaging evaluation during abdominal pain episodes or performing diuretic‐enhanced imaging modalities to capture the structural changes between the episodes. This study comprehensively discussed the diagnostic challenges associated with pediatric intermittent UPJO. We also present a known case of recurrent abdominal pain initially diagnosed as abdominal migraine, which was later reclassified as intermittent UPJO. Moreover, we reviewed the conventional diagnostic approaches in identifying the presence of structural etiologies in intermittent UPJO.